International continence society guidelines on urodynamic equipment performance. Issue 4 (4th January 2014) - Gammie, Andrew; Clarkson, Becky; Constantinou, Chris; Damaser, Margot; Drinnan, Michael; Geleijnse, Geert; Griffiths, Derek; Rosier, Peter; Schäfer, Werner; Van Mastrigt, Ron; ,
<x xml:space="preserve">Abstract</x> These guidelines provide benchmarks for the performance of urodynamic equipment, and have been developed by the International Continence Society to assist purchasing decisions, design requirements, and performance checks. The guidelines suggest ranges of specification for uroflowmetry, volume, pressure, and EMG measurement, along with recommendations for user interfaces and performance tests. Factors affecting measurement relating to the different technologies used are also described. Summary tables of essential and desirable features are included for ease of reference. It is emphasized that these guidelines can only contribute to good urodynamics if equipment is used properly, in accordance with good practice. Neurourol. Urodynam. 33:370–379, 2014. © 2014 Wiley Periodicals, Inc.